Pesticide Residues - Frederick M. Fishel (EDIS)
This fact sheet discusses factors that affect residues of pesticides, including the reasons for their persistence and means to avoid their hazards.  This document is PI-69, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: September 2005.